Arnold Bôcklin’s ‘Im Spiel der Wellen’ as Interpreted in Music by Composers Ludomir Różycki and Max Reger. A Contribution to the Theory and History of Musical Ekphrasis - Gmys, Marcin (Interdisciplinary Studies in Musicology, 2018)
.